Ubiquitous Computing for Remote Cardiac Patient Monitoring: A Survey - Sunil Kumar; Kashyap Kambhatla; Fei Hu; Mark Lifson; Yang Xiao (International Journal of Telemedicine and Applications)
New wireless technologies, such as wireless LAN and sensor networks, for telecardiology purposes give new possibilities for monitoring vital parameters with wearable biomedical sensors, and give patients the freedom to be mobile and still be under continuous monitoring and thereby better quality of patient care. This paper will detail the architecture and quality-of-service (QoS) characteristics in integrated wireless telecardiology platforms. It will also discuss the current promising hardware/software platforms for wireless cardiac monitoring. The design methodology and challenges are provided for realistic implementation.